2017
DOI: 10.1111/jocd.12400
|View full text |Cite
|
Sign up to set email alerts
|

Growing evidence of the beneficial effects of a marine protein‐based dietary supplement for treating hair loss

Abstract: A dietary supplement containing a marine complex and other natural ingredients can safely and effectively promote hair growth and decrease hair shedding in women and men with thinning hair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…They found the treatment group exhibited increases in total hair count, total hair density, and terminal hair density, in addition to improved visual assessment of hair growth by study investigators [96]. Additionally, key reviews by Hornfeldt et al in 2015 andHornfeldt in 2018 further details an open-label pilot study by Stephens et al and numerous subsequent randomized, double-blind, control trials, investigating the ability of an oral marine formulation, particularly Viviscal ® (Lifes2good, Inc., Chicago, IL), to treat hair thinning in both males and females [97,98]. These studies utilized oral marine supplement containing shark and mollusk powder, silica, and acerola cherry-based Vitamin C, biotin, and zinc [97,98].…”
Section: Marine Supplements For Treating Hair Lossmentioning
confidence: 97%
See 2 more Smart Citations
“…They found the treatment group exhibited increases in total hair count, total hair density, and terminal hair density, in addition to improved visual assessment of hair growth by study investigators [96]. Additionally, key reviews by Hornfeldt et al in 2015 andHornfeldt in 2018 further details an open-label pilot study by Stephens et al and numerous subsequent randomized, double-blind, control trials, investigating the ability of an oral marine formulation, particularly Viviscal ® (Lifes2good, Inc., Chicago, IL), to treat hair thinning in both males and females [97,98]. These studies utilized oral marine supplement containing shark and mollusk powder, silica, and acerola cherry-based Vitamin C, biotin, and zinc [97,98].…”
Section: Marine Supplements For Treating Hair Lossmentioning
confidence: 97%
“…In addition to cell culture and murine models, clinical studies have also been conducted testing the efficacy of marine nutraceuticals in treating various forms of hair loss [96,97,98]. Ablon et al utilized a randomized, double-blind, placebo-controlled trial to investigate the ability of a marine supplement to treat thinning hair in men [96].…”
Section: Marine Supplements For Treating Hair Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Two double‐blind, placebo‐controlled studies have observed that this supplement can increase the number of terminal hairs in women with thinning hair (32%‐211% increase) after 3 months of treatment and improve self‐assessment scores. The beneficial effects of this formulation have been observed for 180 days …”
Section: Therapeuticsmentioning
confidence: 99%
“…The beneficial effects of this formulation have been observed for 180 days. [47][48][49][50][51][52] Other miscellaneous nutraceuticals include those with DHT-inhibitory activity (ß-sitosterol, biochanin A, polysorbate 60, serenoa repens, curcuma aeruginosa, biochanin A), anti-inflammatory activity (ketoconazole, roxithromycin, zinc pyrithione), improved perifollicular vascularization (glyceroloxyesters and silicium, niacin derivatives, prostaglandins), and improved hair follicle nutrition (amino acids, vitamins, trace elements). 53 Other products include hibiscus, oral marine extract, melatonin, oral millet seed, proanthocyanidins, red ginseng, tretinoin, and valproic acid, which demonstrate limited evidence in the literature.…”
Section: Ther Apeuti C Smentioning
confidence: 99%